2021
DOI: 10.3390/insects12030222
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Global Distribution of Sirex juvencus (Hymenoptera: Siricidae) under Near Current and Future Climatic Conditions as Predicted by the Maximum Entropy Model

Abstract: Wood wasp species in the genus Sirex are known pests of forestry. They cause significant economic losses due to their impacts on plant health and wood quality. S. juvencus (Hymenoptera: Siricidae), widely distributed in Asia, Europe, and North America, is known to negatively impact forestry, infesting Picea, Pinus, Larix, Abies, Cupressus, and Pseudotsuga species. This pest destroys plants by depositing eggs, mucus, and its obligate mutualistic fungus, Amylostereum areolatum. Its obligate mutualistic fungus is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In this study, the AUC value was selected as the index to evaluate the accuracy of the model ( Figure S1 ). The greater the AUC value in the prediction results, the better the prediction effect, where an AUC value of 0.1–0.6 represents the failure of the prediction, 0.6–0.7 represents a poor prediction effect, 0.7–0.8 represents a moderate prediction effect, 0.8–0.9 represents a good prediction effect, and 0.9–1 represents an excellent prediction effect [ 45 , 46 ]. The simulation results showed that the AUC value of the test set was 0.983 in the current period ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the AUC value was selected as the index to evaluate the accuracy of the model ( Figure S1 ). The greater the AUC value in the prediction results, the better the prediction effect, where an AUC value of 0.1–0.6 represents the failure of the prediction, 0.6–0.7 represents a poor prediction effect, 0.7–0.8 represents a moderate prediction effect, 0.8–0.9 represents a good prediction effect, and 0.9–1 represents an excellent prediction effect [ 45 , 46 ]. The simulation results showed that the AUC value of the test set was 0.983 in the current period ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, climatic changes displaced other species, such as sandflies ( Psychodidae ) ( Moo-Llanes et al 2013 ) and the invasive species of the tropical fire ant, Solenopsis geminata (Fabricius) ( Hymenoptera , Formicidae ) ( Lee et al 2021 ). Therefore, environmental modifications caused by climate change, particularly changes in rainfall and temperature patterns, would influence the survival capacity of insects by affecting their reproductive performance, the survival of their larvae and symbiotic or mutualistic interactions with other organisms ( Mellanby et al 1967 , Hurlbert and Liang 2012 , Gao and Shi 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the default parameters of the MaxEnt model were predominantly used in previous studies, which could lead to excessive model fitting [50,51]. To solve this problem, adjusted RM and FC parameters in the MaxEnt model would reduce the complexity and model overfitting in the species distribution [52,53]. This study used the ENMeval packet based on R developed by Muscarella et al [36] to optimize the MaxEnt model parameters.…”
Section: Discussionmentioning
confidence: 99%